The Compliance Model as an Instigation for Post-Financial Crisis Efficiency in Corporations - Ositashvili, Magda (European Scientific Journal, ESJ, 2024)
This paper examines how the compliance model improves corporate governance and efficiency post-financial crisis. This paper focuses on the goals of the compliance model, the strategies for its integration into corporate governance structures, as well as the results and conclusions. The compliance model prioritizes legal and regulatory compliance, ethical standards, and best practices in corporate governance. This methodology helps organizations prevent wrongdoing, enhance transparency, and build stakeholder confidence. Mixed methods study evaluates the compliance model. First, it reviews the theoretical and practical consequences of the compliance model. Next, a quantitative analysis compares pre- and post-compliance model performance metrics in a sample of firms. Finally, qualitative interviews with key stakeholders assess the impact of the model. This study shows that the compliance approach boosts post-financial crisis corporate efficiency. The approach improves corporate governance, malfeasance, and efficiency. Organizations with a culture of compliance, honesty, and responsibility gain stakeholder trust. The results show that the compliance model can help companies revive their corporate governance practices following financial crises. This methodology reduces risks, ensures legal and ethical compliance, and boosts efficiency and effectiveness. This study emphasizes the role of the compliance model in post-financial crisis corporate efficiency. It highlights the favorable effects of the model on corporate governance and organizational success. The report adds to the corporate governance literature and offers practical advice for companies trying to improve their governance in a complicated business environment.